VD_FINDINFO HC / 2011 / 461 vom 17. August 2011 - VD Tribunal cantonal (2011)
DÉTENTION AUX FINS D'EXPULSION, PROPORTIONNALITÉ, RISQUE DE FUITE | 76 al. 1 let. b ch. 3 LEtr, 76 al. 1 let. b ch. 4 LEtr, 79 LEtr, 30 al. 2 LVLEtr, 31 al. 1 LVLEtr, 31 al. 2 LVLEtr